Phytochemical Investigations of Caesalpinia digyna Root - R. Srinivasan; M.J.N. Chandrasekar; M.J. Nanjan (E-Journal of Chemistry)
Phytochemical examination of petroleum ether extract of Caesalpinia digyna root resulted in the isolation of four compounds namely, friedelin, hexacosanoic acid, β-sitosterol and stigmasterol. These compounds have been characterized on basis of physical and spectral data. All the four compounds are being reported for the first time from this plant